The quality of territorial governance: an assessment of institutional arrangements. The case of the Serrano cheese production in the Campos de Cima da Serra, Southern Brazil - Pachoud, Carine (DIE ERDE – Journal of the Geographical Society of Berlin, 2020)
Territorial governance is of growing interest in an endogenous development perspective, in which organizational and institutional arrangements are supplied by the actors themselves to ensure coordination. This study was carried out in the Campos de Cima da Serra in southern Brazil, where the Serrano cheese is produced. It is an informal production. In fact, new consumers’ preferences for young instead of matured cheese, and national hygiene standards that are incompatible with small-scale and artisanal production make the legalization of the sales impossible for the producers. The aim of the study is twofold. First, it brings forward the territorial and value chain governance approaches from French and German-speaking literatures. Second, based on the analysis of institutional arrangements, it assesses the quality of territorial governance processes. For that end, the institutional arrangements implemented in the states of Santa Catarina and Rio Grande do Sul, in the Campos de Cima da Serra, were analyzed. Results show that two different strategies are adopted: In Santa Catarina, there is a strong coordination between all municipalities, whereas in Rio Grande do Sul, municipalities are acting independently, leading to less effective governance. However, institutional arrangements in both states are facing a lack of dynamism. They suffer especially from little mobilization of producers and little involvement of local authorities. The extension services are the central actors of the collective action, following a top-down model. Thus, the achievement of collective action would require more participatory governance through the integration of the different actors in the process, as well as support from the larger institutional environment.